Optimisation of histamine reduction in kawakawa (Euthynnus Affinis) by red grape juice using Response Surface Methodology (RSM) / Ruhaizan Wook - Wook, Ruhaizan (Faculty of Applied Sciences, 2008)
The purpose of this study was to optimise the histamine reduction in kawakawa by red grape juice using Response Surface Methodology (RSM) of MINITAB Software (Version 14). Experimental design was created by RSM whereby test variables; concentration of red grape juice (%), temperature of storage (°C) and time of storage (hrs). One side part flesh of kawakawa were blended, mixed thoroughly in different concentrations of red grape juice and treated differently in terms of temperature and time as suggested by the experimental design of RSM. Histamine analysis was carried out according to AOAC Official Method (1990) and measured using Flouresence Spectrometry. Histamine content in kawakawa was reduced by 78.44% at the optimum condition; 26.4% of concentration red grape juice, storage temperature of -0.2°C and storage time of 56.1 hours. In addition, the significant regression equations or models at the 5% level of confidence was also established for the estimation of the percentage reduction of histamine in kawakawa treated by red grape juice. This indicates that red grape juice is a potential source to be employed to reduce histamine in kawakawa.